Activist-Students: Radical Adult Education from Community to Campus – and Back Again - Donna Chovanec; Lee Ellis; Natasha Goudar; Evelyn Hamdon; Zenobia Jamal; Colin Piquette (Adult Education Research Conference, 2007)
A panel of activist-students, each in a different phase of their academic study of adult education, use their own experiences to examine critical questions about the relationship between theory and practice in radical adult education.